TACSTD2 upregulation is an early reaction to lung infection - Lenárt, Sára; Lenárt, Peter; Knopfová, Lucia; Kotasová, Hana; Pelková, Vendula; Sedláková, Veronika; Vacek, Ondřej; Pokludová, Jana; Čan, Vladimír; Šmarda, Jan; Souček, Karel; Hampl, Aleš; et al. (Scientific reports, 2022)
TACSTD2 encodes a transmembrane glycoprotein Trop2 commonly overexpressed in carcinomas. While the Trop2 protein was discovered already in 1981 and first antibody-drug conjugate targeting Trop2 were recently approved for cancer therapy, the physiological role of Trop2 is still not fully understood. In this article, we show that TACSTD2/Trop2 expression is evolutionarily conserved in lungs of various vertebrates. By analysis of publicly available transcriptomic data we demonstrate that TACSTD2 level consistently increases in lungs infected with miscellaneous, but mainly viral pathogens. Single cell and subpopulation based transcriptomic data revealed that the major source of TACSTD2 transcript are lung epithelial cells and their progenitors and that TACSTD2 is induced directly in lung epithelial cells following infection. Increase in TACSTD2 expression may represent a mechanism to maintain/restore epithelial barrier function and contribute to regeneration process in infected/damaged lungs.
Keywords: Animals; plíce; Antigens, Neoplasm; zvířata; Lung; Epithelial Cells; upregulace; antigeny nádorové; epitelové buňky; Cell Adhesion Molecules; molekuly buněčné adheze; Up-Regulation